Current strategies for the treatment of intermediate and advanced hepatocellular carcinoma. (January 2020) - Vogel, Arndt; Saborowski, Anna
Highlights: Several new substances have substantially changed the field of systemic therapy for patients with HCC. Locoregional therapies will remain a mainstay of HCC therapy, but recent phase-III trials advocate for a more cautious use. Preservation of liver function will be pivotal for a successful sequential administration of therapies. The combination of bevacizumab and atezolizumab marks the transition from TKI monotherapy to immunotherapy-based combination therapies in the treatment of HCC. The field still lacks predictive biomarkers that can be used to guide proper choice of therapy in routine clinical practice. Abstract: Hepatocellular carcinoma (HCC) ranks among the most common cancers worldwide and remains to be a major global health care problem. Until 2007, no effective therapies were available for patients after failure of locoregional approaches, and the approval of sorafenib as the first systemic agent with efficacy in patients suffering from advanced HCC marked a new era in the treatment of this deadly disease. However, it took nearly 10 years until the portfolio of effective drugs finally expanded and additional substances showed activity in both first and further lines of treatment. Since their recent approval, these novel substances have substantially changed the field of palliative treatment strategies in patients with advanced HCC, and their sequential application has demonstrated their potential to significantly prolong patient survival in the palliative setting. With the recently communicated data from the first positive immuno-oncology trial in HCC, it appears highly likely that the implementation of IO concepts will result in a further improvement of patient prognosis. Although locoregional approaches remain an integral component of meaningful treatment concepts for patients with BCLC-B stage HCC, repetitive interventions bear the risk of a progressive deterioration of liver function. More than ever, in order to implement long-term therapeutic concepts and exploit the full potential of systemic treatment strategies, it is of utmost importance to maintain a fine balance between anti-tumor activity and toxicity. With an emphasis on the systemic treatment options, this review provides a summary of the most recent results from large phase III clinical trials and discusses their clinical implications.